The emergence of the Levallois technology in the Levant: A view from the Early Middle Paleolithic site of Misliya Cave, Israel. Issue 144 (July 2020) - Zaidner, Yossi; Weinstein-Evron, Mina
Abstract: The Early Middle Paleolithic (EMP) lithic assemblage of Misliya Cave, dated to 240–150 ka, is associated with one of the earliest occurrences of Homo sapiens outside Africa. Our research provides a detailed technological study of the lithic assemblage of stratigraphic unit 5–6c of the site, using the chaîne opératoire approach, to characterize the technological behavior of the early H. sapiens . Our results indicate that both Levallois and laminar volumetric concepts were used. The Levallois reduction strategy involved preparing subtriangular cores with steep distal edges that allowed producing a series of triangular/subtriangular Levallois blanks using a unidirectional convergent method. Laminar débitage constitutes a semirotating/rotating method. The results of our study and comparisons with other Levantine sites indicate that the EMP represents a distinct entity within the Levantine Middle Pleistocene record that can be distinguished by the earliest occurrence of a full-fledged Levallois technology in the region, laminar technology, and a distinct tool kit dominated by elongated retouched points. The level of core management involved in producing convergent Levallois products and in preparing laminar cores points to a major conceptual change from the preceding Acheulian and Acheulo-Yabrudian. This suggests a break in knapping strategies between the Lower and the Middle Paleolithic. The finding of a H. sapiens maxilla at Misliya Cave in association with the EMP industry supports the hypothesis that the introduction of the Levallois technology in the Near East was associated with an early dispersal of H. sapiens from Africa. A comparison between the Levantine EMP and other regional records indicates that different Levallois methods were routinely used by hominins from the beginning of the Middle Paleolithic and the Middle Stone Age.